PELAKSANAAN E-GOVERNMENT DI PEMERINTAH DAERAH KABUPATEN PONOROGO : Array - Dian Suluh Kusuma Dewi; Dwiana Binti Yulianti; Ekapti Wahjuni Djuwitaningsih (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2021)
Immigration in Indonesia continues to strive to innovate in immigration services by utilizing developments in information systems and technology to facilitate immigration services and improve the bureaucratic system. The online passport queue registration system has been implemented at the Class III Non-TPI Ponorogo Immigration Office since the issuance of the Circular of the Directorate General of Immigration Number IMI-UM.01.01-4166 concerning the Implementation of Online Passport Application Queue Registration Applications throughout Indonesia. The application of this online passport queue registration system has been realized by the Non TPI Ponorogo Class III Immigration Office since 2017. With the online passport queue registration system, the public can more easily register queues and get information related to when to come to the Non-Class III Immigration Office. TPI Ponorogo made a passport. How is the application of egovernment in the online passport queue registration system at the Class III NonTPI Ponorogo Immigration Office? This type of research is qualitative research with a descriptive approach. The Online Passport Queue Registration Application (APAPO) as a form of e-government practice in its application in society has been able to improve the quality of effective, efficient, transparent and accountable government administration with non-stop service interactions. The pattern whereby the user or applicant can access this application anywhere as long as the user or applicant is connected to an internet connection. The Online Passport Queue Registration Application (APAPO) is able to reduce queuing time for passport processing so that applicants do not have to queue for a long time because with this application applicants can find out the arrival hours at the immigration office and this application is quite informative for its users.